Study on the SHP2-Mediated Mechanism of Promoting Spermatogenesis Induced by Active Compounds of Eucommiae Folium in Mice - Mu, Hailong; Liu, Shuangshi; Tian, Shiyang; Chen, Beibei; Liu, Zengyuan; Fan, Yunpeng; Liu, Yingqiu; Ma, Wuren; Zhang, Weimin; Fu, Mingzhe; Song, Xiaoping (Frontiers in Pharmacology, 2022)
Spermatogenesis directly determines the reproductive capacity of male animals. With the development of society, the increasing pressure on people's lives and changes in the living environment, male fertility is declining. The leaf of Eucommia ulmoides Oliv. (Eucommiae Folium, EF) was recorded in the 2020 Chinese Pharmacopoeia and was used in traditional Chinese medicine as a tonic. In recent years, EF has been reported to improve spermatogenesis, but the mechanisms of EF remain was poorly characterized. In this study, the effect of EF ethanol extract (EFEE) on spermatogenesis was tested in mice. Chemical components related to spermatogenesis in EF were predicted by network pharmacology. The biological activity of the predicted chemical components was measured by the proliferation of C18-4 spermatogonial stem cells (SSCs) and the testosterone secretion of TM3 leydig cells. The biological activity of chlorogenic acid (CGA), the active compound in EF, was tested in vivo. The cell cycle was analysed by flow cytometry. Testosterone secretion was detected by ELISA. RNA interference (RNAi) was used to detect the effect of key genes on cell biological activity. Western blotting, qRT–PCR and immunofluorescence staining were used to analyse the molecular mechanism of related biological activities. The results showed that EFEE and CGA could improve spermatogenesis in mice. Furthermore, the main mechanism was that CGA promoted SSC proliferation, self-renewal and Leydig cell testosterone secretion by promoting the expression of SHP2 and activating the downstream signaling pathways involved in these biological processes. This study provided strong evidence for elucidating the mechanism by which EF promotes the spermatogenesis in mice and a new theoretical basis for dealing with the decrease in male reproductive capacity.